Long-term follow-up after aneurysm treatment with the Flow Redirection Endoluminal Device (FRED) flow diverter - Hohenstatt, Sophia; Ulfert, Christian; Herweh, Christian; Hilgenfeld, Tim; Schmitt, Niclas; Schönenberger, Silvia; Chen, Min; Bendszus, Martin; Möhlenbruch, Markus Alfred; Vollherbst, Dominik (Clinical neuroradiology, 2023)
This study focuses on long-term outcomes after aneurysm treatment with either the Flow Re-Direction Endoluminal Device (FRED) or the FRED Jr. to investigate the durability of treatment effect and long-term complications.